DETERMINASI PENGAMBILAN KEPUTUSAN PENGELUARAN: PERAN LITERASI KEUANGAN, PENCATATAN KEUANGAN DAN SKALA PRIORITAS (STUDI KASUS KARYAWAN PERGURUAN TINGGI) - Hadijah Sitti; Wa Ode Sartika; Harpiang Wardiningsih; Perduti Lestari Rulimo; Rahmah Djauzyah Patola (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to know the influence of financial literacy, financial recording, and priority scale on expenditure decision-making among university employees. A quantitative approach with a survey method was employed, and data were collected through questionnaires distributed to university employees via google form. The data were analyzed using correlation techniques with SPSS software. The results show that financial literacy has a very strong and significant relationship with expenditure decision-making, followed by priority scale, and financial recording with a moderate relationship. These findings suggest that financial literacy and priority scale are the dominant factors determining the quality of expenditure decision-making, while financial recording serves as a supporting factor. This study contributes to the development of literature on individual financial behavior in higher education institutional settings.